Analysis of Strategic Planning and the Role of Managers in Improving Nursing Resource Performance: Systematic Review - Wildan Wildan; Hanny Handiyani; Hening Pujasari; Kuntarti Kuntarti (GLOBAL HEALTH SCIENCE GROUP, 2025)
The success of health organizations depends on the quality of human resources including nursing resources. Health organizations can grow and develop if they have staff or nurses with demonstrated high performance. Good performance is directly proportional to the quality of services provided. Performance appraisal is very important to evaluate, assess and measure, to enhance employee capabilities and professionalism. This assessment aims to ensure that organizational goals can be achieved optimally. Furthermore, strategic planning and the role of managers are essential in performance appraisal. With good strategic planning, supported by the optimal role of managers, can enhance staff performance and facilitate the achievement of organizational objectives. Managers who have good abilities in planning, organizing, staffing, actuating and controlling the vision, mission and goals of the organization can be achieved. Objective: This study aims to determine the relationship strategic planning and the role of managers on the performance of nursing resources. Methods : This systematic review was prepared based on Preferred Reporting Items for Systematic Reviews and Meta-Analyzes (PRISMA). Used databases Scopus, ProQuest, Science Direct, Pubmed, Clinicalkey and Google Scholar. Articles used from 2023-2025. Keywords Strategic Planning AND Manager Roles AND Performance Appraisal for Nurses. Joanna Briggs Institute (JBI) and Critical Appraisal Skills Program (CASP) analysis. From 78,200 articles found, 8 articles were analyzed. The results of systematic analysis in the study showed that with appropriate strategic planning and good manager roles can improve nurse performance which has an impact on improving the quality of service and the goals and vision of the organization's mission can be achieved. The results of the study can be concluded that strategic planning and the role of managers have a significant effect on improving performance so that organizational goals can be achieved optimally.